A thin dark line : a novel - Hoag, Tami (Bantam Books, 2017)
In Louisiana, Deputy Sheriff Annie Broussard catches Detective Renard beating a man the whole town believes is guilty of murder even though a court acquitted him. Annie arrests Renard, only to become ostracized by the town and suspended from the police department. But Renard too is suspended and in a twist of fate the pair must join forces to investigate the murder anew.